(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article explores the process of shaping students’ physical competence in higher education institutions through innovative pedagogical methods, interactive approaches, simulations, and virtual laboratories. The article also analyzes the process of teaching students to apply their knowledge through pedagogical methods such as problem-based learning (PBL) and flipped classroom. According to the results of research, these methods enhance the students’ ability to grasp physical concepts and prepare them for real-life situations. The article provides comprehensive information on the practical results of the innovative technologies and methods used in the educational process and their role in developing students’ competence.